Pola Hubungan Makan Dengan Pencegahan Gastritis dari SMK Antartika 2 Sidoarjo - Fauziah F. Hernanto (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
Gastritis is an inflammation that affects the gastric mucosa that can lead to swelling of the stomach that concerns the most important cause in the gastrointestinal tract. Gastritis disease occurs in people who have an irregular diet and eat foods that stimulate the production of stomach acid. This study aims to determine Relationship Pattern Eating With Prevention Gastritis Of SMK Antartika 2 Sidoarjo. The method used in this research is Cross Sectional approach. Sampling technique used is simpling with sample research counted 30 respondents at On Student Faculty Of Health Sciences University Independent Surabaya. Data collection by using questionnaires for diet and gastritis. Technique of chi square got result p significant value p